2017
DOI: 10.2174/1567201813666160712164149
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Tumor-Specific Immunity by p5 HER-2/neu Generated Peptide Encapsulated in Nano-liposomes with High Phase Transition Temperature Phospholipids

Abstract: The results indicated that simple liposomes consisting of phospholipids with high transition temperature could be an effective vaccine vehicle for tumor-associated antigens for inducing cell mediate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…2,27 It was also reported that the formulation of P5 peptide encapsulated in DSPC:DSPG nanoliposomes could significantly induce IFN-γ secretion and antigen-specific CTL responses, which led to a lower tumor size and a longer survival time when compared with the control group. 21 Similarly, our results also showed that P5-peptideconjugated liposomal formulation composed of DSPC, DSPG, Chol, and DOPE (Tm: 54°C) containing MPL could efficiently stimulate CTL responses against TUBO tumor cells. According to a previous study, immunogenicity of P5 peptide was enhanced via conjugation of P5 on the surface of liposome nanoparticles (DMPC; DMPG; Chol).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…2,27 It was also reported that the formulation of P5 peptide encapsulated in DSPC:DSPG nanoliposomes could significantly induce IFN-γ secretion and antigen-specific CTL responses, which led to a lower tumor size and a longer survival time when compared with the control group. 21 Similarly, our results also showed that P5-peptideconjugated liposomal formulation composed of DSPC, DSPG, Chol, and DOPE (Tm: 54°C) containing MPL could efficiently stimulate CTL responses against TUBO tumor cells. According to a previous study, immunogenicity of P5 peptide was enhanced via conjugation of P5 on the surface of liposome nanoparticles (DMPC; DMPG; Chol).…”
Section: Discussionsupporting
confidence: 72%
“…DSPC‐contained liposome formulations have been found to be significantly effective in stimulating Th1 and CTL responses to both entrapped and membrane‐linked antigens . It was also reported that the formulation of P5 peptide encapsulated in DSPC:DSPG nanoliposomes could significantly induce IFN‐γ secretion and antigen‐specific CTL responses, which led to a lower tumor size and a longer survival time when compared with the control group …”
Section: Discussionmentioning
confidence: 97%
“…On the basis of Mansourian, making use of chaotropic transfer technique, new researches from Yazdani et al. ( 2017 ) made liposomes with high transition temperature (T m ) to sustain the stability, in the function of a vaccine for P5 HER2/neu generated peptide. After evaluation, especially in experiments in vivo the results suggested that immunization with Lip-p5 nanoliposomes has enhanced the antigen-specific IFN-γ response of CD8 + T cells and induced CTL response in comparison with free peptides and empty liposomes, which resulted in a smaller tumor and longer survival time.…”
Section: Examples Of Applications In Nano Peptide Tumor Vaccinesmentioning
confidence: 99%
“…Increasing cellular and humoral response against HER2/neu has been associated with decreased tumor development and improved prognosis [24]. In our previous study, several HER2/neu epitopes were formulated in different nanoliposomes, which could induce effective immune responses against HER2-positive murine tumor model [25][26][27][28]. Our findings demonstrated that P435, as a short HER2 epitope, was an effective peptide which inducing CTL responses and improving prognosis of cancer in TUBO mice model of breast cancer [29].…”
Section: Introductionmentioning
confidence: 99%